Catalytic Activities of Au6, Au 6−, and Au 6+ Clusters for CO oxidation: A density functional study. Issue 22 (19th June 2014) - Baishya, Subhi; Deka, Ramesh C.
<x xml:space="preserve">Abstract</x> We have studied the CO oxidation over neutral, anionic, and cationic gold hexamer clusters using density functional theory which elucidates the effect of cluster charge state on the catalytic activity. Herein, we have considered the conventional bimolecular Langmuir–Hinshelwood mechanism with coadsorbed CO and O2 at the neighboring sites in all the clusters. Among the three clusters, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdc3pkn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Au 6−</alternatives> entails lower barriers during the various steps of the oxidation mechanism. The stability of all the species including the transition states with respect to the interacting species in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdc3q1b" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Au 6−</alternatives> indicates no thermal activation. Our study suggests better catalytic activity of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fdc3q63" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Au 6−</alternatives> as compared to the neutral and cationic counterparts. © 2014 Wiley Periodicals, Inc.